2015
DOI: 10.1021/acs.jpcc.5b01738
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Ni Clusters and the Adsorption of CH4: First-Principles Calculations

Abstract: Structural, magnetic and adsorption properties of Ni n (n = 2−16, 21, 55) clusters have been investigated based on density funciontal theory (DFT) with the spin polarized generalized gradient approximation, using the Perdew−Burke−Ernzerhof functional. The most stable isomers have been selected to study the adsorption of methane CH 4 and methyl CH 3 . It is found that the CH 4 molecule adsorbs on the top site for all clusters considered. The most selective Ni n clusters are the tetrahedron (n = 4) and icosahedr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 51 publications
(98 reference statements)
3
12
0
Order By: Relevance
“…An interesting feature is that the oxygen chemisorption leads to a stabilization of an icosahedral Ni core in all configurations observed. The same is seen in two studies which found the capped bipyramid cluster to be the ground-state geometry: with CH 4 adsorption [48] or with one atom substituted by Fe, Co, or Ru, [46] the cluster core is stabilized in the icosahedral configuration.…”
Section: Ni 13 Cluster Chemisorption: One O 2 Moleculesupporting
confidence: 70%
See 1 more Smart Citation
“…An interesting feature is that the oxygen chemisorption leads to a stabilization of an icosahedral Ni core in all configurations observed. The same is seen in two studies which found the capped bipyramid cluster to be the ground-state geometry: with CH 4 adsorption [48] or with one atom substituted by Fe, Co, or Ru, [46] the cluster core is stabilized in the icosahedral configuration.…”
Section: Ni 13 Cluster Chemisorption: One O 2 Moleculesupporting
confidence: 70%
“…[39,40] It is expected that the icosahedral cluster is the ground-state structure, [20,[40][41][42][43] but previous theoretical studies found that this is not the case. Instead, it was proposed that distorted [44,45] or the capped bipyramid (hexagonal close-packed) clusters [46][47][48] be the ground-state geometry. To elucidate this situation, we reproduced these results.…”
Section: Pristine Ni 13 Clustersmentioning
confidence: 99%
“…1a,b) show average Ni-Ni bond lengths of 2.31Å and 2.37Å, respectively, and magnetic moments per Ni atom of 1.4 µ B and 0.9 µ B , in agreement with previous calculations. 31,32 The density of states (DOS) ( Fig. 1c,d) demonstrates that the We calculate the storage capacities of the Ni x clusters (x = 6, 13) by adding H molecules, one at a time,allowing the system to structurally relax after each addition.…”
Section: Methodsmentioning
confidence: 99%
“…at a finite temperature (T ) and pressure (p). To better understand the situation theoretically, we consider a prototypical model system of nickel (Ni 4 , which is already experimentally synthesized and is having high selectivity [45][46][47] ) in a reactive atmosphere of O 2 and CH 4 gas molecules under realistic conditions. Note that Ni-based catalysts, owing to their low cost, high selectivity and high activity, have been extensively employed experimentally in catalysis over the past.…”
Section: Introductionmentioning
confidence: 99%